2009
DOI: 10.1186/1471-2318-9-s1-a11
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy in the elderly

Abstract: ObjectiveThe purpose of this study was to evaluate the outcome of laparoscopic cholecystectomy in patients age 70 and older with gallstone disease. We reviewed our experience with the laparoscopic procedure underlining the results of laparoscopic cholecystectomy in the geriatric population in term of mortality and complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the study by Story et al, 20% of patients developed at least one complication within 5 days following surgery, and 5% died within 30 days after surgery (32). The study by Fukuse et al examining patients older than 60 years reported that postoperative complications occurred in 16.7% of patients (16), while the study by Zappulla et al analyzing patients aged more than 70 years indicated even a lower complication rate (10%) (5). The above data show that complication rates vary across different studies depending on different pathologies and complications analyzed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study by Story et al, 20% of patients developed at least one complication within 5 days following surgery, and 5% died within 30 days after surgery (32). The study by Fukuse et al examining patients older than 60 years reported that postoperative complications occurred in 16.7% of patients (16), while the study by Zappulla et al analyzing patients aged more than 70 years indicated even a lower complication rate (10%) (5). The above data show that complication rates vary across different studies depending on different pathologies and complications analyzed.…”
Section: Discussionmentioning
confidence: 98%
“…In older age, a decline in functional reserve, impaired reaction to stress, and comorbidities lead to increased postoperative complication and rehospitalization rates, longer duration of postoperative treatment, and higher costs of treatment (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%